Clinical neurophysiology - edited by Kenneth M. Heilman; Edward Valenstein (Oxford University Press, 2003)
This edition, like prior editions, describes the classical signs and symptoms associated with the major behavioral disorders such as aphasia, agraphia, alexia, amnesia, apraxia, neglect, executive disorders and dementia. It also discusses advances in assessing, diagnosing and treating these disorders and it addresses the brain mechanisms underlying these deficits. A multi-authored text has the advantage of having authorities write about the disorders in which they have expertise. The fourth edition adds new authors and five entirely new chapters on phonologic aspects of language disorders, syntactic aspects of language disorders, lexical-semantic aspects of language disorders, anosognosia, hallucinations and related conditions. This is the most comprehensive edition of this text to date